A3_8 Lunar Magnetic Fields? - Manley, Max; Flood, Laura; Holland, Katie; Leversha, Thomas (Physics Special Topics, 2022)
In this paper, we explore the effect that a lunar magnetic field would have on the magnitude of the Earth’s magnetic field at the surface. This was achieved by performing coordinate transformations to give a resultant magnetic field strength at the Earth, which was then used to create plots of the resultant magnetic field strength with altered values for radius and orbital radius of the Moon. From these, we have deduced that, for a lunar magnetic field to have a significant effect on the surface of the Earth, its orbital radius would need to be decreased by a factor of 1E4. Alternatively, the Moon’s radius would have to be increased by a factor of a million.